2014
DOI: 10.1093/ejcts/ezu239
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and severity of primary graft dysfunction after lung transplantation using rejected grafts reconditioned with ex vivo lung perfusion†

Abstract: The use of initially rejected grafts treated with EVLP does not increase the incidence and severity of PGD after LTx. Although comparison of PGD 3 incidence in the two groups did not reach a statistical difference, all EVLP patients suffering from severe PGD early after transplant recovered normal lung function at 72 h, suggesting a protective role of EVLP against PGD occurrence and severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 16 publications
3
40
0
3
Order By: Relevance
“…Consistently, the synthases involved in large-sized HA polymerization were found to be up-regulated in homogenates of perfused lungs, whereas the shorter-chain HA synthase was downregulated. These observations suggest that production of high-MW HA could represent a potential mechanism that underlies the beneficial influences of EVLP observed in lung transplantation (10)(11)(12). Indeed, high-MW HA was shown to exert various protective effects in different lung injury models (22) and after orthotopic lung transplantation (27).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Consistently, the synthases involved in large-sized HA polymerization were found to be up-regulated in homogenates of perfused lungs, whereas the shorter-chain HA synthase was downregulated. These observations suggest that production of high-MW HA could represent a potential mechanism that underlies the beneficial influences of EVLP observed in lung transplantation (10)(11)(12). Indeed, high-MW HA was shown to exert various protective effects in different lung injury models (22) and after orthotopic lung transplantation (27).…”
Section: Discussionmentioning
confidence: 87%
“…Recent evidence suggests that EVLP actions likely exceed evaluation/reconditioning influences. Indeed, ex vivoperfused marginal lungs demonstrated a reduced incidence of primary graft dysfunction compared with untreated standard organs (10,11). Of interest, the transplantation outcome of ex vivo-perfused optimal lungs was also improved compared with lungs subjected to standard procurement (12).…”
mentioning
confidence: 99%
“…The authors did not find any differences between the study groups in term of each grade of PGD as well as extracorporeal membrane oxygenation requirement. One interesting point in this study was the influence of EVLP on a relatively lower volume center: EVLP resulted in a 22% increase in LTx volume through a successful donor lung recondition rate of 73% .…”
Section: Clinical Experience With Evlp: State Of the Artmentioning
confidence: 98%
“…In a prospective non-randomized trial by the Toronto Lung Transplant Program, 15% of recipients of lungs maintained with EVLP developed PGD as compared to 30% in the control non-EVLP group (p=0.11) [33]. Another study by an Italian group showed a similar trend towards a reduction in PGD in lungs reconditioned by EVLP [34]. Since lungs can be maintained on EVLP for at least 12–24 hours, EVLP can extend the time available for assessment of donor lungs to determine suitability for transplantation [35].…”
Section: Ex Vivo Lung Perfusion and Lung Reconditioningmentioning
confidence: 99%
“…EVLP can limit the time of injurious cold ischemia, another known operative risk factor for PGD [3, 36, 37]. In early studies, despite an extended total ischemic time, EVLP has not increased the incidence of PGD [34, 3840]. …”
Section: Ex Vivo Lung Perfusion and Lung Reconditioningmentioning
confidence: 99%